Supporting neurodivergent talent: ADHD, autism, and dyslexia in physics and space sciences - Turner, Niescja E.; Smith, Heather Haynes (Frontiers in Physics, 2023)
Diversity, equity, inclusion, and belonging efforts must include disability and neurodivergence. While there is a long history of famous scientists being identified or speculatively indicated to be neurodivergent, identification on an individual basis has been limited until fairly recently.Definitions have changed and broadened, and people are being identified or are identifying themselves as neurodivergent and are learning about their paths and their brains in a way that was unavailable to people two decades ago. In the contemporary physics or space science classroom or workplace, we have both a responsibility to include and support our neurodivergent learners and scientists, as well as an opportunity to use insights from the neurodiversity movement to better support our teams and students. Herein we explain the language used to describe neurodivergent traits and offer strategies and ideas to support our neurodivergent community members. These strategies include ideas for supporting executive function as well as tips in the areas of physical comfort and sensory considerations.